2018
DOI: 10.1007/s10433-018-0467-2
|View full text |Cite
|
Sign up to set email alerts
|

Grandparenting, education and subjective well-being of older Europeans

Abstract: We study whether grandparenthood is associated with older people's subjective well-being (SWB), considering the association with life satisfaction of having grandchildren per se, their number, and of the provision of grandchild care. Older people's education may not only be an important confounder to control for, but also a moderator in the relation between grandparenthood-related variables and SWB. We investigate these issues by adopting a crosscountry comparative perspective and using data from the Survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 53 publications
7
87
0
9
Order By: Relevance
“…The between-person models indicated the results across participants, that is, between grandparents and nongrandparents; we found that the group of grandparents reported a higher quality of life and life satisfaction than the group of nongrandparents. Thus, these between-person results correspond with prior studies, which have detected that grandparents have better subjective well-being than nongrandparents (e.g., Arpino et al, 2018;Powdthavee, 2011; but see Danielsbacka & Tanskanen, 2016). Moreover, we found no striking sex differences in the between-person models.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The between-person models indicated the results across participants, that is, between grandparents and nongrandparents; we found that the group of grandparents reported a higher quality of life and life satisfaction than the group of nongrandparents. Thus, these between-person results correspond with prior studies, which have detected that grandparents have better subjective well-being than nongrandparents (e.g., Arpino et al, 2018;Powdthavee, 2011; but see Danielsbacka & Tanskanen, 2016). Moreover, we found no striking sex differences in the between-person models.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to within-person regressions, we ran betweenperson models that compare self-rated life satisfaction, quality of life scores, and depressive symptoms among grandparents and non-grandparents. Here, we present the between-person results to allow comparison of our findings with those of previous studies that have analyzed differences between the two groups: grandparents and non-grandparents (e.g., Arpino et al, 2018;Danielsbacka & Tanskanen, 2016;Powdthavee, 2011). This also establishes whether the between-person association exists in this sample before the within-person analysis is conducted.…”
mentioning
confidence: 87%
“…For example, Danielsbacka and Tanskanen (2016) showed that being a grandparent is not associated with either higher or lower happiness among older Finns. Arpino et al (2018) reached similar conclusions for life satisfaction, using data on several European countries. Christiansen (2014) found a higher mortality risk for grandfathers (but not grandmothers) as compared to their grandchildless counterparts in Norway.…”
Section: Grandparenthood and Depressionsupporting
confidence: 63%
“…In particular, grandmothers on average provide more grandchild care than grandfathers. Although little has been done to explain such a gender gap (an exception is the work by Leopold and Skopek 2014), as highlighted by Arpino et al (2018), it is more and more relevant to shed light on the grandparent-related gender gap in view of the increasing grandmothers' participation in the workforce that will make women more likely than men to experience competing roles in later life.…”
Section: The Gendered Dimensions Of Grandparenthoodmentioning
confidence: 99%
See 1 more Smart Citation